Istikhdām Tharīqah At-Tahqiq Al-Jamā'ī (Investigasi Kelompok) wa Hil Al-Musykilāt (Pemecahan Masalah) Li Tarqiyati Mahārah Al-Kalām Ladai At-Tullab fi Al-Madrasah Al-'Aliyah - Henti Marlina; Asrina; Mahyudin Ritonga (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
The main purpose of the study was to determine the effect of using group investigation and problem solving on speaking skills of twelfth grade students of the darurrisalah padang hunik school. This study used quantitative research using experimental methods. Data collection are tests and observations. Data analysis is used with normality, homogeneity and hypothesis test. The results of this study show that the of speaking skills before using group investigation and problem solving is still low. With pre-test results in the experimental class obtained a an average score of 71,07 and in the control class an average score of 70.76. As for the use of group investigation and problem solving on speaking skills with a value of 3.4% very good. Then the post-test results in the experimental class got an average of 86.78 and in the control class got an average value of 76,92. and the result of hypothesis using the t-test obtained thitung = 3.9167 and ttable = 2,060. If tcount > ttable or 2,060> 3.9167, accept Ha means that there is Effect of The Effect of group investigation and problem solving methods to improve students' speaking skills at the Darurrislah Padang Hunik school.